2021
DOI: 10.33891/fsz.114.2.83-91
|View full text |Cite
|
Sign up to set email alerts
|

A periimplantitis sebészi kezelése air-abrasive technológia alkalmazásával

Abstract: Az implantációkkal kapcsolatos biológiai szövődmények közé soroljuk a periimplantaris mucositist és a periimplantitist.A periimplantaris gyulladások gyógyulását konzervatív és különböző sebészi beavatkozásokkal is elősegíthetjük,azonban mindegyik kezelési metódus fontos alappillére, hogy a gyulladt periimplantaris szöveteket és az implantátumsupraossealis részét megtisztítsuk. A nemzetközi irodalomban számos közlemény vizsgálja a különböző airabrasiverendszerek alkalmazását a periimplantaris gyulladások terápi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…During measurement of points with the endodontic gauge, differences were found between ISO and actual sizes, regardless of the point's size and taper. The results obtained in the current study are in line with those obtained by Ivanyj et al [17], Cunha et al [19] and Cunningham et al [20]. The study by Cunha et al [19] showed discrepancies in terms of accuracy of standardised diameters with respect to GP points of 3 different brands, including those manufactured by Dentsply Maillefer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…During measurement of points with the endodontic gauge, differences were found between ISO and actual sizes, regardless of the point's size and taper. The results obtained in the current study are in line with those obtained by Ivanyj et al [17], Cunha et al [19] and Cunningham et al [20]. The study by Cunha et al [19] showed discrepancies in terms of accuracy of standardised diameters with respect to GP points of 3 different brands, including those manufactured by Dentsply Maillefer.…”
Section: Discussionsupporting
confidence: 90%
“…Even though producers guarantee compliance with ISO standards, the dimensions of guttapercha points may differ. There are reports in the literature on the wide variability in diameter and taper of commercially available gutta-percha points [15][16][17]. However, only a few papers address the accuracy of the greater taper GP points [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%